A composite of ultra-fine few-layer MoS2 structures embedded on N, P-co-doped bio-carbon for high-performance sodium-ion batteries. (22nd January 2020) - Luo, Fenqiang; Xia, Xinshu; Zeng, Lingxing; Chen, Xiaochuan; Feng, Xiaoshan; Wang, Jianbiao; Xu, Lihong; Qian, Qingrong; Wei, Mingdeng; Chen, Qinghua
Abstract : Highly dispersed ultra-fine few-layer MoS2 embedded on N/P co-doped bio-carbon composite (MoS2 -N/P-C) was synthesized and it delivers excellent high-rate long term cycling performance (175 mA h g −1 after 2000 cycles at 5 A g −1 ). Abstract : A sustainable and easy method for the fabrication of a composite of ultra-fine few-layer MoS2 structures embedded on N, P-co-doped bio-carbon (MoS2 -N/P-C) was developed by using natural chlorella as an adsorbent and reactor. This MoS2 -N/P-C composite was easily synthesized by carrying out a biosorption of chlorella and a subsequent calcination process. This bio-carbon made from chlorella acted as a nanoreactor to prevent the MoS2 nanoparticles from agglomerating with each other during the calcination process. Besides, the N, P-codoped bio-carbon contributed to the relatively high conductivity and surface wettability of this composite and accommodated the large radius of Na + . When used as an anode for sodium ion batteries, it showed significant superiority with a high rate and long-duration cycling performance, evidenced by a measured capacity of 175 mA h g −1 after 2000 cycles at 5 A g −1 .